2012
DOI: 10.1242/jeb.075655
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and molecular chaperone defenses during estivation and arousal in the South American apple-snailPomacea canaliculata

Abstract: SUMMARYThe invasive Pomacea canaliculata estivates during periods of drought and should cope with harmful effects of reoxygenation during arousal. We studied thiobarbituric acid reactive substances (TBARS), enzymatic (superoxide dismutase, SOD and catalase, CAT) and non-enzymatic antioxidants (uric acid and reduced glutathione), and heat shock protein expression (Hsc70, Hsp70 and Hsp90) in (1) active control snails, (2) snails after 45days of estivation, and (3) aroused snails 20min and (4) 24h after water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 64 publications
3
50
0
1
Order By: Relevance
“…Reduced glutathione also seems to participate as an antioxidant in the activityaestivation cycle. Furthermore, changes in the expression of molecular chaperones (Hsc 70, Hsp 70s, Hsp 90) indicate they may participate in protecting the proteome during aestivation and arousal (Giraud-Billoud et al, 2013b). Sun et al (2013) quantified and compared 701 proteins isolated from P. canaliculata during the activity-aestivation cycle, revealing 53 proteins that were differentially regulated during the cycle.…”
Section: Aestivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced glutathione also seems to participate as an antioxidant in the activityaestivation cycle. Furthermore, changes in the expression of molecular chaperones (Hsc 70, Hsp 70s, Hsp 90) indicate they may participate in protecting the proteome during aestivation and arousal (Giraud-Billoud et al, 2013b). Sun et al (2013) quantified and compared 701 proteins isolated from P. canaliculata during the activity-aestivation cycle, revealing 53 proteins that were differentially regulated during the cycle.…”
Section: Aestivationmentioning
confidence: 99%
“…No such organs have been found in P. canaliculata, although spheroidal hemocyte aggregates, similar to those formed in vitro (Cueto et al, 2013), were found in the lung following injection of yeast cells into the visceral hump (Rodriguez et al, 2012), suggesting a role of the hemocytes in fighting infection. Also, large hemocyte islets occupy the hemocoelic spaces in the kidney of P. canaliculata (Cueto, 2011;Giraud-Billoud et al, 2013b;Cueto et al, submitted), and it is possible that they function as a hemocyte-producing organ. Also, hemocyte spheroids are formed in these islets after the injection of yeast cells in the foot (Rodriguez et al, 2012), demonstrating the reactivity of the islets to an immune challenge.…”
Section: Hemocyte-producing Organs And/or Immune Barriersmentioning
confidence: 99%
“…It has already been shown that both Hsps and antioxidant defence are included in the response to stress during cycles of aestivation and arousal in gastropods (Storey and Storey, 2011;Giraud-Billoud et al, 2013). However, protein biosynthesis is a costly process, especially under stressful conditions, and it is thought that Hsp70 expression is very energy costly (Sanchez et al, 1992;Heckathorn et al, 1996;Köhler et al, 2000).…”
Section: Research Articlementioning
confidence: 99%
“…One may argue that this effect may be due to an energetic trade-off between Hsp70 and antioxidants, in the same way that, in consequence, energy is spent in the biosynthesis of enzymatic antioxidants (here CAT) instead of Hsp70. As suggested by Giraud-Billoud et al (Giraud-Billoud et al, 2013), antioxidants and chaperone-mediated protective mechanisms such as Hsp70 may work independently, but the activation of different stress-response pathways is promoted by reactive metabolites of oxidative stress. Gorman et al (Gorman et al, 1999) examined the hypothesis that ROS contribute to the induction of Hsps during stress response and found that the tested antioxidants caused a reduction or complete inhibition of Hsp induction.…”
Section: Research Articlementioning
confidence: 99%
“…The hepatopancreas was selected for analysis as this organ is important for energy metabolism and waste storage, and its protein expression has been shown to be responsive to another environmental stressor (desiccation). [44][45][46] Protein extraction, digestion and labelling Samples were placed on ice to reduce the influence of heat. Hepatopancreas tissues were homogenized using a plastic pestle.…”
Section: Protein Expressionmentioning
confidence: 99%